Genotype-phenotype correlation in a family with late onset CMT and an MPZ lys236del mutation. Issue 3 (16th February 2005) - Sowden, J E; Logigian, E L; Malik, K; Herrmann, D N
Abstract : An in frame, lys236 deletion in the intracytoplasmic domain of myelin protein zero (MPZ) has recently been designated as a mutation possibly associated with Charcot-Marie-Tooth disease (CMT) but requiring further documentation. In this report we present a detailed clinical, electrophysiological, and genotype correlation in three generations of a family with the MPZ lys236del mutation and provide further evidence that this mutation is associated with CMT. The MPZ lys236del mutation is associated with an autosomal dominant, adult onset CMT phenotype, with variable penetrance ranging from an asymptomatic state to foot deformities, pedal numbness, and muscle cramps. Nerve conduction studies disclose intermediate range, somewhat non-uniform slowing of motor nerve conduction, which is accentuated in forelimb rather than distal nerve segments. Based on the contrasting finding of entirely normal conduction velocities (CV) in a genetically affected 15 year old in this family, it remains to be established whether CV slowing with this mutation is progressive in life, a pattern that would contrast with CMT1a (PMP22 gene duplication).